High catalytic activity at low temperature in oxidative dehydrogenation of propane with Cr–Al pillared clay - de León, María Andrea (2013)
A montmorillonite was pillared separately with chromium and aluminum polyoxocations (Cr–C and Al–C respectively) and also with an equimolar mixture of both polioxocations (Al–Cr–C). The resulting solids were characterized by scanning electron microscopy, energy dispersive spectrometry, thermal analysis, Fourier transform infrared spectroscopy, X-ray diffraction and nitrogen adsorption at −196 °C. The inclusion of polycations in the interlamellar space led to modifications in the properties of the clay. An eleven fold increase in specific surface area with respect to the calcined starting clay was found for the Al–C, whereas a twofold increase was observed for the Cr–C; the value for the Al–Cr–C was only slightly higher than that for the latter. Diffractograms of the Cr–C showed the occurrence of a Cr2O3 phase. Catalytic activity in oxidative dehydrogenation of propane was assayed in the temperature range from 350 °C to 450 °C using Ar/C3H8/O2 (80/10/10) as reactant gas mixture. Propylene selectivity was found to be temperature-dependent, showing a maximum in the studied temperature range for the catalyst containing only aluminum, whereas remaining practically constant for the Cr-containing catalysts. Highly promising propylene yields at low temperature were obtained with the catalyst containing Al and Cr (Al–Cr–C): 9.3% at 350 °C and 10.3% at 450 °C.